Stakeholder Perspectives on Triage in Wildlife Monitoring in a Rapidly Changing Arctic - Wheeler, Helen C.; Berteaux, Dominique; Furgal, Chris; Parlee, Brenda; Yoccoz, Nigel G.; Grémillet, David (Frontiers in Ecology and Evolution, 2016)
Monitoring activities provide a core contribution to wildlife conservation in the Arctic. Effective monitoring which allows changes in population status to be detected early, provides opportunities to mitigate pressures driving declines. Monitoring triage involves decisions about how and where to prioritise activities in species and ecosystem based monitoring. In particular, monitoring triage examines whether to divert resources away from species where there is high likelihood of extinction in the near-future in favour of species where monitoring activities may produce greater conservation benefits. As a place facing both rapid change with a high likelihood of population extinctions, and serious logistic and financial challenges for field data acquisition, the Arctic provides a good context in which to examine attitudes toward triage in monitoring. For effective decision-making to emerge from monitoring, multiple stakeholders must be involved in defining aims and priorities. We conducted semi-structured interviews with stakeholders in arctic wildlife monitoring (either contributing to observation and recording of wildlife, using information from wildlife observation and recording, or using wildlife as a resource) to elicit their perspectives on triage in wildlife monitoring in the Arctic. The majority (56%) of our 23 participants were predominantly in opposition to triage, 26% were in support of triage and 17% were undecided. Representatives of Indigenous organisations were more likely to be opposed to triage than scientists and those involved in decision-making showed greatest support for triage amongst the scientist participants. Responses to the concept of triage included that: 1) The species-focussed approach associated with triage did not match their more systems-based view (5 participants), 2) Important information is generated through monitoring threatened species which advances understanding of the drivers of change, responses and ecosystem consequences (5 participants), 3) There is an obligation to try to monitor and conserve threatened species (4 participants), and 4) Monitoring needs to address local people’s needs which may be overlooked under triage (3 participants). The complexity of decision-making to create monitoring programmes that maximise benefits to biodiversity and people makes prioritisation with simple models difficult. Using scenarios to identify desirable trajectories of Arctic stewardship may be an effective means of identifying monitoring needs.